Manipulating metabolic partitioning in transgenic plants - Sonnewald, Uwe; et al. (Trends in Biotechnology, 1996)
Various strategies can be used to influence the partitioning of metabolites, both between competing pathways and within a given biochemical pathway. Changes in metabolic partitioning in transgenic plants can be brought about by either expressing heterologous genes or suppressing endogenous ones. Strategies for altering metabolic partitioning can include accelerating, circumventing or inhibiting enzymatic, regulatory or transport steps. In addition, metabolic pathways can be modified, through the use of collections of novel enzymes, to synthesize novel products.